Association of Frailty with Delayed Recovery of Gastrointestinal Function after Elective Colorectal Cancer Resections. Issue 6 (2nd July 2020) - Gong, Wenbin; Qi, Xing
Abstract: Frailty is characterized by a state of vulnerability to poor resolution of homoeostasis after a stressor event and is a consequence of age-related decline in many physiological systems during a lifetime. To access the association between frailty and delayed recovery of gastrointestinal function in patients undergoing elective colorectal cancer resections, 241 patients who had undergone elective colorectal cancer resections from July 2015 to August 2017 were investigated. The association of frailty with delayed recovery of gastrointestinal function, length of stay (LOS), and whether or not to transfer into intensive care unit (ICU) were analyzed. For the entire cohort, 164 (68.0%) of total patients experienced the early recovery of gastrointestinal function, 67 (27.8%) delayed recovery, and 10 (4.1%) patients occurred postoperative ileus (POI) or anastomotic leakage (AL). Low Modified Frailty Index (mFI) score was associated with statistically decreased odds ratios of 0.276 (95% CI, 0.095–0.808; p = 0.019) for delayed recovery of gastrointestinal function or even the occurrence of POI or AL, and shorter LOS of 1.058 (95%CI, 1.024-1.216; p = 0.039) compared with those of high mFI scores. However, mFI scores were not predictive of transferring into ICU (OR, 1.103; 95% CI, 0.808–1.507; p = 0.44). Frailty was associated with increased odds of delayed gastrointestinal function recovery or even the occurrence of POI or AL. Moreover, higher mFI was also associated with longer LOS, but was not predictive of whether or not transferring into ICU.